2019 IEEE MTT-S International Conference on Microwaves for Intelligent Mobility (ICMIM) 2019
DOI: 10.1109/icmim.2019.8726765
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Closely Adjacent Extended Objects in Radar Images using Velocity Profile Analysis

Abstract: As high resolution automotive radars become more common, so does their usage for next-generation functionalities like advanced driver assistant systems and autonomous driving. This creates the need for robust clustering techniques to distinguish among multiple extended objects like vehicles in the same scenario. One especially challenging scenario is that of separating two extended targets close to each other, each following its own trajectory. This paper proposes a clustering algorithm based on the analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…With only radar data of a single frame, Kellner et al [16,17] compute full velocity of moving vehicles from radial velocities and azimuth angles of at least two radar hits. However, for a robust solution, the method requires that 1) radar captures more radar hits on each object, 2) radar points have significantly different azimuth angles and 3) object points are clustered before velocity estimation [16,32,31]. Obviously due to sparsity of radar in a single frame, it is difficult to obtain at least two radar hits on distant vehicles, let alone objects of smaller sizes.…”
Section: Velocity Estimation In Perception Systemsmentioning
confidence: 99%
“…With only radar data of a single frame, Kellner et al [16,17] compute full velocity of moving vehicles from radial velocities and azimuth angles of at least two radar hits. However, for a robust solution, the method requires that 1) radar captures more radar hits on each object, 2) radar points have significantly different azimuth angles and 3) object points are clustered before velocity estimation [16,32,31]. Obviously due to sparsity of radar in a single frame, it is difficult to obtain at least two radar hits on distant vehicles, let alone objects of smaller sizes.…”
Section: Velocity Estimation In Perception Systemsmentioning
confidence: 99%
“…Multiple recent publications have dealt with improvements in object-based, dynamic environment models. This mainly includes the grouping of radar targets to the corresponding object [1], the estimation of object geometry and state of motion [2], and finally their assignment to an object class, such as pedestrian or car [3]- [5]. For fully autonomous driving, however, the creation of a static environment model is also indispensable, for example, to identify the road course ahead according to the infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Eryildirim and Guldogan proposed a method to track a single extended target based on Bernoulli filter [22], [23]. Schlichenmaier et al identified two closely adjacent extended targets based on the analysis of target velocity profile [24]. By knowing the number of extended target, Lan and Li presented an approach for classifying extended object using random matrix and target size provided [25].…”
Section: Introductionmentioning
confidence: 99%